Optimizing the Role of Libraries to Strengthening Literacy at MIN 1 Surabaya - Vita Sari, Nurul; Juhaeni, Juhaeni; Chasanah, Uswatun (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2025)
Literacy serves as a crucial foundation for students' academic success and personal development, particularly at the elementary education level. This study aims to analyze the role of the library at Madrasah Ibtidaiyah Negeri (MIN) 1 Surabaya in supporting student literacy development. Employing a qualitative descriptive approach, this research examines literacy programs, resource availability, and perceptions of students and teachers regarding the library's function as a literacy center. The findings indicate that the MIN 1 Surabaya library implements various strategic initiatives, such as providing diverse reading collections, the